Targeted delivery of antisense oligonucleotides to hepatocytes using triantennary N-acetyl galactosamine improves potency 10-fold in mice. Issue 13 (3rd July 2014) - Prakash, Thazha P.; Graham, Mark J.; Yu, Jinghua; Carty, Rick; Low, Audrey; Chappell, Alfred; Schmidt, Karsten; Zhao, Chenguang; Aghajan, Mariam; Murray, Heather F.; Riney, Stan; Booten, Sheri L.; et al.
Abstract: Triantennary N -acetyl galactosamine (GalNAc, GN3 ), a high-affinity ligand for the hepatocyte-specific asialoglycoprotein receptor (ASGPR), enhances the potency of second-generation gapmer antisense oligonucleotides (ASOs) 6–10-fold in mouse liver. When combined with next-generation ASO designs comprised of short S -cEt ( S -2′- O -Et-2′, 4′-bridged nucleic acid) gapmer ASOs, ∼60-fold enhancement in potency relative to the parent MOE (2′- O -methoxyethyl RNA) ASO was observed. GN3 -conjugated ASOs showed high affinity for mouse ASGPR, which results in enhanced ASO delivery to hepatocytes versus non-parenchymal cells. After internalization into cells, the GN3 -ASO conjugate is metabolized to liberate the parent ASO in the liver. No metabolism of the GN3 -ASO conjugate was detected in plasma suggesting that GN3 acts as a hepatocyte targeting prodrug that is detached from the ASO by metabolism after internalization into the liver. GalNAc conjugation also enhanced potency and duration of the effect of two ASOs targeting human apolipoprotein C-III and human transthyretin (TTR) in transgenic mice. The unconjugated ASOs are currently in late stage clinical trials for the treatment of familial chylomicronemia and TTR-mediated polyneuropathy. The ability to translate these observations in humans offers the potential to improve therapeutic index, reduce cost of therapy and support a monthly dosing schedule for therapeutic suppression of gene expression in the liver using ASOs.